Efficacy of amisulpride for depressive symptoms in individuals with mental disorders: A systematic review and meta‐analysis. (3rd June 2021) - Zangani, Caroline; Giordano, Barbara; Stein, Hans‐Christian; Bonora, Stefano; D'Agostino, Armando; Ostinelli, Edoardo Giuseppe
Abstract: Background: Depressive symptoms occur in several psychiatric disorders, often in the absence of a formal diagnosis of depression. We aimed to evaluate the efficacy and the tolerability of amisulpride, both alone and as augmentation therapy, in the treatment of depressive symptoms in individuals with any major psychiatric disorder. Methods: We searched PubMed, Embase, PsycINFO, GreyLit, OpenGrey and ProQuest up to March 2020 for randomised controlled trials focussing on the treatment of an acute depressive episode in any major psychiatric disorder. A random‐effect meta‐analysis was performed to synthesize the findings on depressive symptoms (primary outcome), response rate and tolerability. Results: We retrieved 11 studies including 2065 patients with a diagnosis of dysthymia (eight studies), major depression (one study) or schizophrenia (two studies). Amisulpride 50 mg/day was associated with a larger reduction of depressive symptoms compared to placebo (standardised mean difference [SMD] = −0.70, CI 95% −0.92, −0.49; I 2 = 0.0%), and was found to be comparable to selective serotonin reuptake inhibitors (SSRIs; SMD = −0.08, CI 95% −0.23, 0.06, I 2 = 0.0%), amineptine, imipramine and amitriptyline in the treatment of dysthymia (three studies, not pooled). In individuals with schizophrenia, amisulpride administered at higher doses (>400 mg/day) was comparable to olanzapine and risperidone (two studies, not pooled). In terms of tolerability, amisulpride was superior to placebo for dysthymia (odds ratio [OR] = 3.94, CI 95% 1.07, 14.48; I 2 = 0.0) and comparable with SSRIs (OR = 0.94, CI 95% 0.55, 1.62; I 2 = 0.0%). Conclusion: Treatment with amisulpride could be a valid choice for selected individuals with dysthymia or depressive symptoms in the context of schizophrenia. More studies on the efficacy and tolerability of amisulpride are needed to draw firm conclusions on its potential benefits in other psychiatric disorders.